The medical clinics of north america - Zimmerman, Hyman (W. B Saunder Companay, 1975)
This book presents knowledge of normal and disordered bilirubin metabolism and of the phenomena and syndromes of cholestasis, which has advanced at a steady rate, is summarized in the three articles.